2017
DOI: 10.4103/ijmy.ijmy_91_17
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of innovative community-based approaches and systematic tuberculosis screening to improve tuberculosis case detection in Ebonyi State, Nigeria

Abstract: Active case-finding strategies achieved good yields though early loss to follow-up was high. Active case finding is recommended for integration into national TB control policy and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…We further discuss our study findings in detail. First, the study had a low rate of PTBP detection, whereas the previous studies on ACF have consistently shown high rates of PTBP detection [23][24][25]. The TAs failed to individually enquire about symptoms that are suggestive of TB from all those who were enumerated.…”
Section: Discussionmentioning
confidence: 89%
“…We further discuss our study findings in detail. First, the study had a low rate of PTBP detection, whereas the previous studies on ACF have consistently shown high rates of PTBP detection [23][24][25]. The TAs failed to individually enquire about symptoms that are suggestive of TB from all those who were enumerated.…”
Section: Discussionmentioning
confidence: 89%
“…Early detection helps to reduce the risks of TB transmission, poor treatment outcomes, undesirable health sequelae, and adverse social and economic consequences of the disease [12]. Studies have shown that community-based systematic screening of HH contacts is feasible and can contribute to improve TB cases finding [13][14][15][16], but it is not practiced in many high burden countries [17].…”
Section: Introductionmentioning
confidence: 99%
“…whereas the previous studies on ACF have consistently shown high rates of PTBP detection [23][24][25].…”
Section: Discussionmentioning
confidence: 75%